E-commerce and Zapato Sanchez, custom shoes: research and exploration - Capito, Sabrina; Garcia, Maria; Hu, Yan; Santiago, Marla; Zwierink, Teagan (My University, 2019)
As e-commerce platforms expand, local businesses are trying to keep up and grow alongside the bigger companies. This research project explored the role of e-commerce and custom-made artisanal dress shoes for a local Edmonton business, specifically investigating if advertising on social media platforms would allow for sales growth.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: Zapato Sanchez; e-commerce; bespoke; customization; Traditionalists; Gen X; Gen Y